EFFECT OF CREDIT RISK AND LIQUIDITY RISK ON PROFITABILITY PEOPLE'S CREDIT BANK IN KUPANG CITY - Enike Tje Yustin Dima; Frederic Winston Nalle (SEAN Institute, 2023)
The banking sector has a very large role in improving the country's economy. Public trust in banking is also getting higher along with the number of BPRs that are mushrooming and the level of competition is also getting more competitive. Therefore, every person's credit institution must also be able to demonstrate its existence with a bank's financial soundness level that can be trusted by the wider community. Realizing this, this study aims to determine the level of credit risk and liquidity risk by looking at the value of Non-Performing Loans and the value of the Loan to Deposit Ratio. The results of financial analysis carried out further calculations to determine the effect of credit risk and liquidity risk variables both partially and simultaneously at the level of BPR profitability in Kupang City. The method of determining the sample used purposive sampling so that the samples in this study were six BPRs. In an effort to answer the research objectives, the analytical tools used are financial analysis and also multiple linear regression analysis. The independent variables in this study are credit risk which is proxied by Non Performing Loans (NPL) and liquidity risk which is proxied by Loan to Deposit Ratio (LDR), as well as the dependent variable which is the Bank's financial performance which is estimated by Return on Assets (ROA). The results showed that partially the Non Performing Loan (NPL) and Loan to Deposit Ratio (LDR) variables had a positive but not significant effect on Return On Assets (ROA).